Reasons for the use of commercial infant formulas in mothers who are users of a primary care facility in Chiclayo- Peru - Cayao Guevara, Katherine Irimar (2025)
Objective: Describe the reasons for the use of commercial infant formulas in mothers who are users of a primary care health facility in Chiclayo-Peru. Method: Qualitative, descriptive study, developed with 16 mothers who attend the José Leonardo Ortiz Health Center, province of Chiclayo, Peru, between March and April 2024, data collection was done using an interview guide, validated by judgment of experts and pilot test, with the approval of the institutional ethics committee. The findings were processed through thematic content analysis. Results: It was found that the most frequent reasons for the use of commercial infant formulas were; low milk production, maternal situations and misperceptions about the composition and benefits of commercial infant formulas. Conclusions: Mothers use commercial infant formulas, given the slightest discouragement in dairy production, driven by their erroneous perceptions about its composition and benefits superior to breast milk, in other cases in particular situations such as: cesarean section, work and studies, that require being addressed individually by the health team.